Patient knowledge about drugs prescribed at primary healthcare facilities - AKICI, AHMET; UĞURLU, MUSTAFA ÜMİT (WILEY, 2004)
Objective Providing adequate information to the patients about their drugs is an essential principle of rational pharmacotherapy. This study investigates the knowledge of general practice patients about their drugs, since the level of knowledge of the patient about the medication is highly associated with the outcome of the therapy. Methods A total of 1618 patients who applied to primary healthcare centers in Istanbul and accepted to participate in the study were asked about the name(s) and effect(s) of the drug(s) on their prescriptions. Factors that might influence the background knowledge and perception of patients such as sociodemographic characteristics, drug-use habits and practitioners' attitudes were also questioned. Information provided by the patients was compared with the prescriptions. Results Only 10.9% of the respondents could recall the names of their drug(s) correctly. Level of education, and gender, had a positive impact on recalling drug names. Patients, who received a refill prescription, with a chronic disease, and who had self-medication before applying to the health center reported more accurate information. Less than half of the practitioners had informed their patients about the drug effects; and 7% of the patients have been requested to repeat the instructions and warnings about his/her medication(s). The patients to name their drugs correctly also knew the drug effects twice as much the patients who could not recall their drug(s)'name. The drugs which were correctly named were the ones used in chronic diseases. Conclusion It appears that patients, particularly who are poorly educated, males, and who received a first prescription know little about their prescribed drugs. These results suggest that patients' education about drugs is an important issue regarding rational drug use which deserves urgent improvement. Copyright (C) 2004 John Wiley Sons, Ltd.
Keywords: drug name; patient knowledge; prescription; medication; rational drug use